How Speech Lost Its Voice: The Informational Turn in US Free Speech Law. - Petersen, Jennifer (History of Humanities)
In influential strains of late twentieth-century US legal discourse on free speech, speech and language have been disconnected from sound, and speech rendered as a form of writing. The effect of this is a free speech jurisprudence in which analysis of speech is less concerned with speakers and more concerned with messages. The article explores this situation by examining the legal reasoning in a 2001 case in which federal district court judges ruled that computer programs written in binary computer code (1s and 0s) were a form of "speech" covered by the First Amendment. They did so by equating speech with writing, drawing on a theorization of language in terms of information rather than as embodied social practice. The article argues that this logic follows the popularization of information theory and the rhetoric of disembodiment that grew out of this popularization in the latter half of the twentieth century.